Answer:
The solution of the given system is (x,y) = (1,4)
Step-by-step explanation:
Here, the given system of equation is:
x = -3 + y
26 x - 5 y = 6
Now, substitute x = -3 + y in the second equation , we get
26 x - 5 y = 6 ⇒ 26 (-3 + y) - 5 y = 6
or, 26(-3) + 26(y) - 5y = 6
⇒ - 78 + 26 y - 5y = 6
⇒ 21 y = 84
⇒ y = 84 / 21 = 4 or , y = 4
So x = -3 + y = -3 + 4 = 1
Hence, the solution of the given system is (x,y) = (1,4)
Answer:
y=x-1
Step-by-step explanation:
Gradient=1
Rise/run=1/1=1
y=x+c
y intercept=-1
y=x-1
Answer: root18
Step-by-step explanation:
A (2,2) x1=2 y1=2
B (5,5) x2=5 y2=5
D(AB) = root [(x2-x1)^2 + (y2-y1)^2]
= root [(5-2)^2 + (5-2)^2]
= root [3^2 + 3^2]
= root (9+9)
D(AB)=root18
mark the brainliest plzz
It is B because tangent lines are always perpendicular to radii
Answer:$724
Step-by-step explanation: so in the first month they charge 149+ 25 which equals 174. then you 25x11 which gets you 275.then you add those 2 and get 449. then you 449 plus 275 and get 724.